Unitary group and quantum group invariant q-oscillators and fibonaccization - Ünel, N. Gökhan. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1994., 1994)
After a review of different types of q-oscillators and the relationship between their creation/ annihilation operators, the derivation of the q generalized version of the LeviCivita tensor (E) is given. The properties of the quantum group SLq(n) are obtained through the invariance properties of the new q-epsilon tensor. The relations between the inner products of n-particle states of the various q-oscillators are also investigated. Finally, a two parameter generalization of the Coon-Baker-Yu q-oscillator (which we call Fibonaccization) is presented.
Keywords: Unitary groups.; Quantum groups.; Quantum theory.